Circular economy approaches for the production of high-value polysaccharides from microalgal biomass grown on industrial fish processing wastewater: A review - Rifna, E.J.; Rajauria, Gaurav; Dwivedi, Madhuresh; Tiwari, Brijesh K. (International journal of biological macromolecules, 2024)
The discharge of high-strength wastewater from the fish-processing industries, comprising undefined blends of toxic and organic compounds, has always been a subject of great disquiet worldwide. Despite a large number of effluent treatment methodologies known to date, biosorption with the aid of naturally grown microalgae has been recognized recently to possess promising outcomes in eradicating pollutants comprising organic compounds from liquid effluents. Interestingly, the microalgal biomass harvested from phytoremediation of fish effluent was identified to be abundant in bio compounds that exhibited potential application in pharmaceutical, nutraceutical, and, aquaculture feed, generating a circular economy. In this context, the focus of the review is to emphasize the applications of microalgal species as naturally occurring and zero-cost adsorbents for the elimination of organic contaminants from fish liquid effluents. The summary of the literature encompassed in this work is supposed to benefit the readers to comprehend the primary mechanisms by which microalgae uptakes the organic matter from fish processing effluents and converts them into various biological molecules. From the scientific works assessed through this review, the most promising microalgae species regards to nutrient uptake and removal efficiency from fish effluent, were identified as Chlorella sp. > Spirulina sp. > Scenedesmus sp. The review further revealed supercritical fluid extraction as the robust extraction tool for the extraction of targeted bioproducts from microalgal biomass grown within fish effluents. Eventually, the information presented through this review establishes phytoremediation using microalgal biomass to be a natural cost-effective, sustainable circular bio-economy approach that could be robustly applied for the efficient treatment of wastewater discharged from food processing industries.